2017
DOI: 10.1117/1.jbo.22.10.105003
|View full text |Cite
|
Sign up to set email alerts
|

Toward jet injection by continuous-wave laser cavitation

Abstract: This is a study motivated by the need to develop a needle-free device for eliminating major global healthcare problems caused by needles. The generation of liquid jets by means of a continuous-wave laser, focused into a light absorbing solution, was studied with the aim of developing a portable and affordable jet injector. We designed and fabricated glass microfluidic devices, which consist of a chamber where thermocavitation is created and a tapered channel. The growth of a vapor bubble displaces and expels t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 59 publications
0
32
1
Order By: Relevance
“…Jets were mostly stopped by the reticular dermis and reached the hypodermis with the efficiency of only 12%. With regard to the diagram presented by Rodríguez et al 18 we can claim, that such shallow penetration prevents this technology from delivering a drug aimed to reach the hypodermis or muscle tissue.…”
mentioning
confidence: 99%
“…Jets were mostly stopped by the reticular dermis and reached the hypodermis with the efficiency of only 12%. With regard to the diagram presented by Rodríguez et al 18 we can claim, that such shallow penetration prevents this technology from delivering a drug aimed to reach the hypodermis or muscle tissue.…”
mentioning
confidence: 99%
“…The fabrication process and design of these devices were previously described elsewhere. 8,9 The microfluidic devices consisted of two rectangular channels with 100 μm depth:…”
Section: Needle-free Micro-jet Injectormentioning
confidence: 99%
“…16,17 From the different energy sources used to power NFIs, a recent example is based on continuous wave (CW) lasers that cause a phenomenon known as thermocavitation to create liquid jets by heating the injectate above its boiling point with an explosive phase transition. 8,9,27,28,35 This work evaluates a CW-based needle-free micro-jet injector as a possible transdermal delivery alternative with minimal damage to the skin structure. For the purpose of this study, the topical solution delivery will be primarily associated with diffusion processes.…”
Section: Introductionmentioning
confidence: 99%
“…Cavitation induced by lasers has been ultimately used for development of technolgies, such as needle free injection [1,2,3] and ink-jet printing [4,5]. Pulsed-laser-based systems produce very fast jets, however they are expensive, noisy, heavy, among others [1,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Cavitation induced by lasers has been ultimately used for development of technolgies, such as needle free injection [1,2,3] and ink-jet printing [4,5]. Pulsed-laser-based systems produce very fast jets, however they are expensive, noisy, heavy, among others [1,6,7]. Recently, it has been demonstrated that continuous wave lasers -which are cheaper, lighter, more portable and with lower safety risks than pulsed lasers-are able to induce jets by cavitation with speeds up to ∼100m/s [1,8], becoming a more efficient alternative for the mentioned technologies.…”
Section: Introductionmentioning
confidence: 99%